Oczekiwania pracowników jako determinanta zmian w systemach wynagradzania - Kopertyńska, Wanda Maria; Kmiotek, Krystyna (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The article describes a connection between employees' expectations and motivation systems in organizations. The employees' expectations are different because they have different needs. It also discusses payment as a tool of the motivation process. The systems of motivation should take into account the employees' expectations. The conclusion is that it is necessary to have a appropriate proportions between employees' expectations and the business targets. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1184, s. 310-316